2020
DOI: 10.1371/journal.pone.0237512
|View full text |Cite
|
Sign up to set email alerts
|

Associations of spousal communication with contraceptive method use among adolescent wives and their husbands in Niger

Abstract: Objectives This study aims to examine associations between spousal communication about contraception and ever use of modern contraception, overt modern contraceptive use (with husband’s knowledge), and covert modern contraceptive use (without husband’s knowledge) among adolescent wives and their husbands in Niger. Study design Cross-sectional data, from the Reaching Married Adolescents Study , were collected from randomly selected adolescent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…While global data shows that many women conceal contraceptive use from their partner, [22][23][24][25] significant research also confirms that in diverse settings, including in Niger, partner communication about contraception is associated with contraceptive continuation. 26,27 The present study confirmed that women feel Caya can be used without their partner's knowledge. However, the study also found examples of how outreach to men led to partner communication and male support for voluntary contraceptive use.…”
Section: Discussionsupporting
confidence: 83%
“…While global data shows that many women conceal contraceptive use from their partner, [22][23][24][25] significant research also confirms that in diverse settings, including in Niger, partner communication about contraception is associated with contraceptive continuation. 26,27 The present study confirmed that women feel Caya can be used without their partner's knowledge. However, the study also found examples of how outreach to men led to partner communication and male support for voluntary contraceptive use.…”
Section: Discussionsupporting
confidence: 83%
“…Other plausible reasons might include gender inequitable norms affecting contraception use among young married women. Young women whose husbands do not support contraceptive use have limited participation and control in decision-making in a marital relationship and low negotiation ( 37 ). Conversations with intimate partners often resulted in consent for contraceptive use ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…women ages 15-49) without a focus on young couples (Bankole, 1995;Baschieri et al, 2013;Speizer, 1999;Takuri, 2012;Tilahun et al, 2014). The few studies of young couples found from LMIC (Challa et al, 2020;Yeatman & Sennott, 2014) do not examine the association between joint fertility desires and contraceptive use. By focusing on young couples, we see that many of these young couples still desire children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Challa and colleagues (2020) examine couples where the wife is aged 15-19 to determine how couple communication about contraception relates to contraceptive use behaviours in Niger. The authors find that less than a quarter of young couples report discussion and that those who discussed are more likely to report contraceptive use, and those who discussed are less likely to use covertly than overtly (Challa et al, 2020). Further, Yeatman and Sennott (2014) examine young couples (i.e.…”
Section: Introductionmentioning
confidence: 99%